Degradation of a Fluorine‐Free Perfluorooctane Sulfonate Substitute in Chromium Plating Solutions. Issue 3 (25th February 2013) - Wienand, N.; Constapel, M.; Budde, K.; Marzinkowski, J. M.; Gäb, S.; Schmitz, O. J.
Abstract Hexavalent chromium solutions for decorative chromium plating in which perfluorooctane sulfonate (PFOS) was replaced by the fluorine‐free oleylamine ethoxylate were investigated. This substitute is degraded under the highly oxidative conditions of chromium plating processes and thus has to be replenished. In both an industrial plant and laboratory experiments the lead anode was found to undergo increased corrosion when oleylamine ethoxylate is used. This lead then precipitates as PbCrO4. The weight loss of the Pb anode was investigated for the use of PFOS and oleylamine ethoxylate as surfactants. It was shown in laboratory experiments that organic substances accumulate in chromium plating solutions with this alternative surfactant. By ion chromatography combined with mass spectrometric detection, dicarboxylates and amino dicarboxylates were identified. However, no negative impact on process safety and product quality could be determined when oleylamine ethoxylate was used. Monitoring of dissolved organic carbon is proposed as a means of assessing a chromium plating solution for organic contamination.